DIAGNOSTIC ACCURACY OF SLIT SKIN SMEARS IN LEPROSY: Slit Skin Smears in Leprosy - Naveed, Tehseen; Shaikh, Zafar Iqbal; Anwar, Muhammad Irfan (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the diagnostic accuracy of slit skin smears in clinically suspected patients of leprosy using histopathology as gold standard. Study Design: Validation study Place and Duration of Study: Study was carried out at Rawalpindi Leprosy Hospital, Dermatology Department Military Hospital (MH) and Armed Forces Institute of Pathology (AFIP), Rawalpindi from 18th August 2012 to 18 Feb 2013. Methods: Appropriate technical and ethical approval for the study and patient consent were obtained. All suspected patients of leprosy of any age and either gender having typical hypo-aesthetic or anesthetic, erythematous or hypo-pigmented scaly skin lesions on any part of body were included in this study. All patients who have already received treatment for leprosy, patients with pure neural leprosy, patient not giving their consent for skin biopsy and patients with lepra reactions were excluded from this study. Forty eight patients fulfilling the inclusion criteria were included in the study. Sample size had been calculated by using WHO sample size calculator taking confidence level 95%, absolute precision required 14% and anticipated population proportion 40%. Non-probability consecutive sampling technique was used to collect sample. Results: The results of the study revealed that out of 48 clinically suspected patients of leprosy skin biopsy confirmed the diagnosis in 34 patients (70.8%) and the slit skin smear had diagnostic accuracy of 68.75% with sensitivity 55.8% and specificity and positive predictive value of 100%. Conclusion: Study suggested that although slit skin smears are rapid and inexpensive method of diagnosis but their diagnostic accuracy is low.